2021
DOI: 10.1002/smtd.202001001
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Organic Framework Hybrids Aid Metabolic Profiling for Colorectal Cancer

Abstract: Colorectal cancer (CRC) is the third most common fatal cancer worldwide, accounting for ≈10% of cancer‐related mortality. Metabolic shift occurs from the very early stage during the development of CRC, which is of significant etiological and diagnostic importance toward precision medicine. Here, an advanced molecular tool to characterize the metabolic alterations in CRC, based on metal‐organic framework (MOF) hybrids is reported. Consuming only 500 nL of plasma without any sample pretreatment, MOF hybrids yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 107 publications
3
32
0
Order By: Relevance
“…The plasma is an alternate bio‐fluid for in vitro metabolic diagnosis. Li et al [84] . presented MIL‐88 A anchored Pt nanoparticles as an advanced matrix to distinguish colorectal cancer by sparse learning algorithm with an AUC value of 0.947/0.912 for the discovery cohort/validation cohort.…”
Section: Application Of Metabolic Analysis In Biological Fluidsmentioning
confidence: 99%
“…The plasma is an alternate bio‐fluid for in vitro metabolic diagnosis. Li et al [84] . presented MIL‐88 A anchored Pt nanoparticles as an advanced matrix to distinguish colorectal cancer by sparse learning algorithm with an AUC value of 0.947/0.912 for the discovery cohort/validation cohort.…”
Section: Application Of Metabolic Analysis In Biological Fluidsmentioning
confidence: 99%
“…MS‐based metabolic fingerprinting have been conducted on the following diseases: cancers (including brain, [8b] lung, [ 20 ] pancreatic, [ 21 ] colorectal, [ 22 ] gastric, [8a,23] cervical, [ 10,24 ] and gynecological cancer [ 25 ] ), inflammatory or infectious disease, [9a,26] kidney disease, [2d] and cardiovascular/cerebrovascular diseases. [ 27 ] Compared with conventional diagnostic imaging and biopsy methods, MS‐based metabolic fingerprinting affords desirable accuracy with minimum invasiveness and low costs.…”
Section: Clinical Application Of Mass Spectrometry‐based Metabolic Fi...mentioning
confidence: 99%
“…Su et al optimized plasmonic alloys to reveal a distinct metabolic phenotype in early gastric cancer . Li et al demonstrated that MOF/Pt hybrid-assisted LDI MS combined with machine learning analysis of the obtained MFs is a powerful method for aiding CRC diagnosis . Imaging tests are also helpful in diagnosing CRC, including computed tomography (CT), nuclear magnetic resonance (NMR), a roentgeno­graphic (Rtg) examination of the thorax, endorectal ultrasonography (USG), and abdominal USG.…”
Section: Introductionmentioning
confidence: 99%
“…11 Li et al demonstrated that MOF/Pt hybrid-assisted LDI MS combined with machine learning analysis of the obtained MFs is a powerful method for aiding CRC diagnosis. 12 Imaging tests are also helpful in diagnosing CRC, including computed tomography (CT), nuclear magnetic resonance (NMR), a roentgenographic (Rtg) examination of the thorax, endorectal ultrasonography (USG), and abdominal USG. However, these methods are efficient only in cases of severe focal lesions or during the middle−late stage.…”
Section: Introductionmentioning
confidence: 99%